2012
DOI: 10.1371/journal.pone.0041568
|View full text |Cite
|
Sign up to set email alerts
|

Private and Public Decisions in Social Dilemmas: Evidence from Children’s Behavior

Abstract: Are selfish impulses less likely to be pursued when decisions are publicly observable? Is the presence of peers a potential solution to social dilemmas? In this paper we report data on the self-control decisions of children aged 6 to 11 who participated in games that require one to resist a selfish impulse for several minutes in order to benefit others. In Public Condition children make decisions in public view of the group of other participants, while in Private Condition they have the possibility to decide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Although Houser et al (2012) did not investigate sex differences in peer monitoring effects in children, our study clearly showed significant differences between boys and girls. This discrepancy may be explained by the different games; while the DG was used in our study to measure children’s generosity, a modified social dilemma game that involved waiting for a reward was used in Houser et al (2012) ’s study. The latter study did not measure children’s generosity per se , but rather their endurance ( Curry et al, 2008 ) and general trust ( Yamagishi, 1988 ).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Although Houser et al (2012) did not investigate sex differences in peer monitoring effects in children, our study clearly showed significant differences between boys and girls. This discrepancy may be explained by the different games; while the DG was used in our study to measure children’s generosity, a modified social dilemma game that involved waiting for a reward was used in Houser et al (2012) ’s study. The latter study did not measure children’s generosity per se , but rather their endurance ( Curry et al, 2008 ) and general trust ( Yamagishi, 1988 ).…”
Section: Discussioncontrasting
confidence: 72%
“…Consistent with this interpretation, Houser et al (2012) demonstrated a peer monitoring effect on contributions to group members using a modified social dilemma game in children 9 years and older. Although Houser et al (2012) did not investigate sex differences in peer monitoring effects in children, our study clearly showed significant differences between boys and girls. This discrepancy may be explained by the different games; while the DG was used in our study to measure children’s generosity, a modified social dilemma game that involved waiting for a reward was used in Houser et al (2012) ’s study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In each of the grades we were testing, silly bandz proved popular (www.sillybandz.com). Several studies have now also used this resource in different economic games with children (e.g., Houser et al, 2012;Maggian & Villeval, 2013, Chen et al 2014Devetag et al, 2013). After running our study, we evaluated the desirability of silly bandz at different ages by comparing the percentage of children who gave all of the items away (max of 4).…”
Section: Dictator Game (Dg)mentioning
confidence: 99%